A New-Sociologist "Makes Peace with" One of his Former Subconscious Role Models. (21st May 2015) - Caya, Sinan
Abstract: This presentation contains extracts from the correspondence between a former-engineer Turkish sociologist and a foreign sociology instructor, with whom he had befriended years ago. At the time, the Turkish sociologist was an engineering student and as such, he used to underestimate sociology. Moreover; he did not even refrain from expressing this openly in his conversations. Years later, though, he wants to find the address of that instructor (now an emeritus professor) and in a sense submit his apology; because, now, let alone appreciating sociology, he himself has obtained a Ph.D. degree in sociology; in the mean time. The need to establish such a dialogue is a compulsory task of reliving his conscience as it would come equal to a professional debt and an ethical self-acquittal.